The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2174/1573399811666150526151241
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions Between Diabetes Mellitus and Myelodysplastic Syndromes: Current State of Evidence and Future Directions

Abstract: Diabetes mellitus (DM) and cancer are disorders of global importance. Multiple epidemiologic studies show that diabetic patients have an increased risk of developing cancer of different types. Myelodysplastic syndromes (MDS) are among the most common hematologic malignancies and include a heterogeneous group of hematopoietic neoplasms characterized by dysplastic changes, low blood counts, and an increased risk of progression to acute myeloid leukemia. Potential epigenetic and metabolic interferences between DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that impaired glucose metabolism in red blood cells, 45 and involvement of glucose metabolism in the erythropoiesis in MDS patients, has already been reported. [46][47][48] MCV in diabetes has been investigated but no definitive conclusions made. Although studies reported on lower MCV, 49,50 others suggested that the hyperosmolarity is associated with an increased MCV.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that impaired glucose metabolism in red blood cells, 45 and involvement of glucose metabolism in the erythropoiesis in MDS patients, has already been reported. [46][47][48] MCV in diabetes has been investigated but no definitive conclusions made. Although studies reported on lower MCV, 49,50 others suggested that the hyperosmolarity is associated with an increased MCV.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple epidemiologic studies show that diabetic patients are more likely to develop cancer [8]. There is also evidence that COVID-19 precipitates DKA due to B-cell destruction from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [7].…”
Section: Discussionmentioning
confidence: 99%
“…The observation of abnormal threonine metabolism to 2,3-DHBA in both children and a dog with IDDM [ 38 ] raises the question as to whether or not our observations of elevated plasma 2,3-DHBA in AML with mutated IDH1/2 could be due to diabetes. The relationship between diabetes mellitus and myelodysblastic syndromes (MDS) has been examined but there is no clear evidence that diabetes is a risk factor for MDS [ 64 ]. MDS can evolve into AML [ 65 ], but only seven of our 51 patients had a previous diagnosis of MDS ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%